PARTICIPACIÓN DE LAS FUERZAS ARMADAS EN ACCIONES DE AYUDA HUMANITARIA Y EL DESARROLLO HUMANO EN LAS LOCALIDADES DEL VALLE DE LOS RÍOS APURÍMAC, ENE Y MANTARO (VRAEM), AF-2019 - Chuquimajo Huamantumba, Johny (2022)
The present article obeys to the research entitled “Participation of the Armed Forces in humanitarian aid actions and human development in the localities of the Apurímac, Ene and Mantaro river valley (VRAEM), FY-2019”, had the general objective of determining the relationship between the humanitarian aid actions of the Armed Forces and human development in the towns of the Apurímac, Ene and Mantaro river valley; A research with a quantitative approach was carried out, the type of research according to its purpose was applied, the research method was the hypothetical deductive one, it was a research of correlational scope and its design was non-experimental with a correlational transectional cut. The population under study was made up of 4384 people, residents in the town of Canayre, the sampling being of a simple random type and comprised 383 people, observation and survey techniques were applied, the instrument used was the Likert-style questionnaire composed of 27 ítems, aimed at people of legal age and with responsibility for family responsibilities. The research, using the SPSS version 25 system for data processing, concluded on the level of correlation between the variables, which was obtained in the study of the Spearman Rho correlation, resulting in a value of 0.713 revealing that there is a coefficient high positive correlation between the participation of the armed forces. in humanitarian aid actions and human development in the towns of the Apurímac, Ene and Mantaro river valley. For a significance level of 95%, according to the 0.000 level of significance, it has been possible to reject the null hypothesis and accept the working hypothesis: there is a significant relationship between the participation of the armed forces. in humanitarian aid actions and human development in the Vraem localities. Keywords: Participation of the Armed Forces, Humanitarian aid, Human development.